Korelasi Distribusi Ukuran mikroplastik dan Parameter Kualitas Air di Hulu Sungai Brantas - Luthfia Ayu Dhea; Andi Kurniawan; Siti Mariyah Ulfa; Karimah Karimah (Jurnal Penelitian Pendidikan IPA, 2023)
Microplastics are contaminants resulting from plastic fragmentation with a size <5 mm. The spread of microplastics threatens the imbalance of the environment and organisms in the waters. So it is necessary to know the abundance, size distribution, and correlation between microplastic abundance and water quality parameters. This study used a quantitative descriptive method with purposive sampling. The study parameters included total microplastic abundance, microplastic abundance based on size characteristics, type of microplastic polymer, water quality parameters, and correlation between microplastic abundance and water quality. Calculating the total abundance of microplastics obtained a value range of 3311.11 – 18111.11 particles/m3. The results of the microplastic size distribution got the highest abundance percentage value in the class with a size <50 µm, which was 84.39%. There were eight types of polymers identified, including Polyethylene (PE), Polyvinyl chloride (PVC), Polypropylene (PP), High-density polyethylene (HDPE), Low-density polyethylene (LDPE, Polyethylene terephthalate (PET), Polycarbonate (PC), and Nylon. Water quality measurements obtained temperature range of 17.37-26.63 °C, pH value range of 6.66-8.51, current velocity value range of 0.13-0.8 m/s, DO value range of 4, 32-6.103 ppm, BOD value range of 4.69-6.07 ppm and TSS value range 0.005-0.019 ppm. Correlation analysis using the Canonical Correlation Analysis (CCA) statistical method. The study showed that water quality parameters such as temperature, current velocity, and DO have a high score of 0.95, 0.83, and 0.8.